Trans-Americanity : subaltern modernities, global coloniality, and the cultures of greater Mexico - Saldívar, José David (New Americanists., 2012)
Saldívar is one of the founders of border studies and one of the most respected senior scholars in American Studies. In this work he introduces the term trans-Americanity as a frame for thinking more hemispherically within a global, world-systems frame.